Kinetics of the hydrogen oxidation reaction on nanostructured rhodium electrodes in alkaline solution - Montero, María de Los Angeles (2015)
The hydrogen oxidation reaction was studied on a nanostructured rhodium electrode at different rotation rates in alkaline solution. The electrode was prepared via sputtering on a glassy carbon disc support and it was characterized by atomic force microscopy and cyclic voltammetry. The real surface area was evaluated by CO stripping voltammetry. Experimental current density (j) – overpotential (η) curves of the hydrogen oxidation reaction were obtained in the range −0.015 ≤ η/V ≤ 0.40 at different rotation rates (900 ≤ ω/rpm ≤ 4900). The resulting curves were correlated by kinetic expressions derived from the Tafel-Heyrovsky-Volmer mechanism with a Frumkin type adsorption of the reaction intermediate and the kinetic parameters were evaluated. It was verified that over this overpotential region the reaction in alkaline solution proceeds mainly through the Tafel-Volmer route. These results were compared with those previously obtained in acid solutions.